The Theory of Planned Behavior model and students' intentions to use bioenergy: A cross-cultural perspective. (April 2016) - Halder, Pradipta; Pietarinen, Janne; Havu-Nuutinen, Sari; Pöllänen, Sinikka; Pelkonen, Paavo
Abstract: The present study tested the Theory of Planned Behavior (TPB) model in explaining high school students' intentions to use bioenergy in Finland and India. Data were collected from 402 Finnish and 130 Indian students studying in the ninth and tenth grades in nine schools. Structural Equation Modeling was applied to test the TPB model. The results revealed that the construct 'Attitude' had the strongest and statistically significant positive effect on the students' intentions to use bioenergy in a cross-cultural setting and also within the Finnish context. The other constructs such as 'Subjective Norm' (SN) showed the second most positive effect on intention, whereas 'Perceived Behavioral Control' (PBC) had a negligible effect on 'Intention'. However, SN was the only construct that had the strongest and statistically significant positive impact on the Indian students' intentions to use bioenergy. The results indicated the applicability of the TPB model in explaining students' intentions to use bioenergy in a cross-cultural context. Future studies could use an extended TPB model by including additional socio-psychological and contextual variables in explaining young students' renewable energy-related behavioral intentions. Highlights: Theory of Planned Behavior model was applied to explain students' intentions to use bioenergy in Finland and India. The effect of 'Attitude' was the strongest on the students' intentions to use bioenergy cross-culturally and in Finland. 'Subjective Norm' had the most substantial impact on the Indian students' intentions to use bioenergy. Utility of the Theory of Planned Behavior model in explaining students' intentions to use bioenergy was confirmed.